Mutations associated with floral organ number in rice - Nagasawa, N; Miyoshi, M; Kitano, H; Satoh, H; Nagato, Y. (Tokyo Univ. (Japan). Faculty of Agriculture) (Planta, 1996)
How floral organ number is specified is an interesting subject and has been intensively studied in Arabidopsis thaliana. In rice (Oryza sativa L.), mutations associated with floral organ number have been identified. In three mutants of rice, floral organ number 1 (fon1) and the two alleles, floral organ number 2-1 (fon2-1) and floral organ number 2-2 (fon2-2), the floral organs were increased in number centripetally. Lodicules, homologous to petals, were rarely affected, and stamens were frequently increased from six to seven or eight. Of all the floral organs the number of pistils was the most frequently increased. Among the mutants, fon1 showed a different spectrum of organ number from fon2 -1 and fon2 -2. Lodicules were the most frequently affected in fon1, but pistils of more than half of fon1 flowers were unaffected; in contrast, the pistils of most flowers were increased in fon2 -1 and fon2-2. Homeotic conversion of organ identity was also detected at a low frequency in ectopically formed lodicules and stamens. Lodicules and stamens were partially converted into anthers and stigmas, respectively. Concomitant with the increased number of floral organs, each mutant had an enlarged apical meristem. Although meristem size was comparable among the three mutants and wild type in the early phase of flower development, a significant difference became apparent after the lemma primordium had differentiated. In these mutants, the size of the shoot apical meristem in the embryo and in the vegetative phase was not affected, and no phenotypic abnormalities were detected. These results do not coincide with those for Arabidopsis in which clavatal affects the sizes of both shoot and floral meristems, leading to abnormal phyllotaxis, inflorescence fasciation and increased floral organs. Accordingly, it is considered that FON1 and FON2 function exclusively in the regulation of the floral meristem, not of the vegetative meristem.